Fasudil Improves Motor Functions Against Rotenone-Induced Neurotoxicity in Rats (Asian Journal of Pharmaceutics (AJP), 2025)
Parkinson’s disease (PD), the second most frequent neurodegenerative disease, involves theprogressive loss of dopaminergic neurons in the substantia Nigra, resulting in motor dysfunction. Recently, Rho-associated protein kinase (ROCK) has been associated with Parkinson’s pathology. Fasudil (FSD), a ROCKinhibitor, offers neuroprotection; however, its precise mechanism remains to be explored in the rotenone (ROT)-exposed animal model. Objectives: This study aimed to evaluate the therapeutic effectiveness of FSD in mitigatingROT -induced neurotoxicity by attenuating oxidative stress (OS) in a Parkinsonian rat model. Materials andMethods: Wistar rats were exposed to ROT (2.5 mg/kg; i.p.,) for 28 days to induce Parkinson’s-like symptoms.Subsequently, FSD (10 mg/kg; p.o.) was administered daily for 28 days in the treatment group. The behavioraland biochemical assessments were conducted to evaluate motor functions, OS, dopamine (DA) levels, andmitochondrial functions. Results: Administration of ROT caused increased motor dysfunction and OS, along witha reduction in dopaminergic content. FSD treatment reversed the motor and biochemical impairments caused byROT by restoring DA levels, enhancing enzymatic antioxidant activity, and reducing lipid peroxidation, therebyprotecting dopaminergic neurons. Conclusion: The present study demonstrated that FSD has a neuroprotectiveeffect in ROT -induced neurotoxicity, mediated by inhibiting the ROCK pathway, which results in the restorationof antioxidant and DA levels.